A national consensus management pathway for paediatric inflammatory multisystem syndrome temporally associated with COVID-19 (PIMS-TS): results of a national Delphi process. (February 2021) - Harwood, Rachel; Allin, Benjamin; Jones, Christine E; Whittaker, Elizabeth; Ramnarayan, Padmanabhan; Ramanan, Athimalaipet V; Kaleem, Musa; Tulloh, Robert; Peters, Mark J; Almond, Sarah; Davis, Peter J; Levin, Michael; et al.
Summary: Paediatric inflammatory multisystem syndrome temporally associated with COVID-19 (PIMS-TS) is a novel condition that was first reported in April, 2020. We aimed to develop a national consensus management pathway for the UK to provide guidance for clinicians caring for children with PIMS-TS. A three-phase online Delphi process and virtual consensus meeting sought consensus over the investigation, management, and research priorities from multidisciplinary clinicians caring for children with PIMS-TS. We used 140 consensus statements to derive a consensus management pathway that describes the initial investigation of children with suspected PIMS-TS, including blood markers to help determine the severity of disease, an echocardiogram, and a viral and septic screen to exclude other infectious causes of illness. The importance of a multidisciplinary team in decision making for children with PIMS-TS is highlighted throughout the guidance, along with the recommended treatment options, including supportive care, intravenous immunoglobulin, methylprednisolone, and biological therapies. These include IL-1 antagonists (eg, anakinra), IL-6 receptor blockers (eg, tocilizumab), and anti-TNF agents (eg, infliximab) for children with Kawasaki disease-like phenotype and non-specific presentations. Use of a rapid online Delphi process has made it possible to generate a national consensus pathway in a timely and cost-efficient manner in the middle of a global pandemic. The consensus statements represent the views of UK clinicians and are applicable to children in the UK suspected of having PIMS-TS. Future evidence will inform updates to this guidance, which in the interim provides a solid framework to support clinicians caring for children with PIMS-TS. This process has directly informed new PIMS-TS specific treatment groups as part of the adaptive UK RECOVERY trial protocol, which is the first formal randomised controlled trial of therapies for PIMS-TS globally.